Protótipo de um microgerador termoelétrico de estado sólido: cogeração a gás - Farias, Sandro Ricardo Alves (2009)
The thermoelectric energy conversion can be performed directly on generators without moving parts, using the principle of SEEBECK effect, obtained in junctions of drivers' thermocouples and most recently in semiconductor junctions type p-n which have increased efficiency of conversion. When termogenerators are exposed to the temperature difference (thermal gradient) eletromotriz a force is generated inducing the appearance of an electric current in the circuit. Thus, it is possible to convert the heat of combustion of a gas through a burner in power, being a thermoelectric generator. The development of infrared burners, using porous ceramic plate, is possible to improve the efficiency of heating, and reduce harmful emissions such as CO, CO2, NOx, etc.. In recent years the meliorate of thermoelectric modules semiconductor (TEG's) has stimulated the development of devices generating and recovery of thermal irreversibility of thermal machines and processes, improving energy efficiency and exergy these systems, especially processes that enable the cogeneration of energy. This work is based on the construction and evaluation of a prototype in a pilot scale, for energy generation to specific applications. The unit uses a fuel gas (LPG) as a primary energy source. The prototype consists of a porous plate burner infrared, an adapter to the module generator, a set of semiconductor modules purchased from Hi-Z Inc. and a heat exchanger to be used as cold source. The prototype was mounted on a test bench, using a system of acquisition of temperature, a system of application of load and instrumentation to assess its functioning and performance. The prototype had an efficiency of chemical conversion of 0.31% for electrical and heat recovery for cogeneration of about 33.2%, resulting in an overall efficiency of 33.51%. The efficiency of energy exergy next shows that the use of primary energy to useful fuel was satisfactory, although the proposed mechanism has also has a low performance due to underuse of the area heated by the small number of modules, as well as a thermal gradient below the ideal informed by the manufacturer, and other factors. The test methodology adopted proved to be suitable for evaluating the prototype